Nuclear Magnetic Resonance Studies of Group V Pentaflourides and Related Compounds - Rao, Uppaluri R. K. (My University, 1966)
19F n.m.r. spectra of the pentafluorides of the group V elements and their variation with temperature have been studied and interpreted.
Theoretical n.m.r. line shapes of 19F coupled to a high-spin nucleus with I = 7/2 and 9/2 have been calculated and their application to the temperature dependence of the 19F n.m.r. spectra in VOF4- and NbF6- respectively has been demonstrated. Temperature dependence of the n.m.r. line shapes of the high-spin nucleus in 11BF3 and VOF4- was studied and it was shown that in each of these species the n.m.r. spectrum of either nucleus can be explained in terms of the same parameters, namely, the coupling constant and relaxation time.
A method for explaining the observed 19F n.m.r. line-widths in VF5 and AsF5 is given.
51V n.m.r. chemical shifts in some vanadium containing compounds were measured and are discussed.
Some remarks are made regarding electric field gradients at the central nucleus in asymmetric molecules and in particular, in 5-cordinate molecules.
Title: Nuclear Magnetic Resonance Studies of Group V Pentaflourides and Related Compounds, Author: Uppaluri R. K. Rao, Location: Thode